PENGARUH DUKUNGAN KELUARGA TERHADAP KESEHATAN FISIK LANSIA DI DUSUN III DESA HUTARAO KECAMATAN BANDAR PULAU KABUPATEN ASAHAN TAHUN 2014 - Sianturi, Efendi (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
The elderly is seen as a group of people who are at risk of experiencing health problems are complexand progressive. One of the many problems that arise in the nursing group is social disorder becausemany things affect this kind of support group members of the family and the environment. Penilitiangoal was to determine the effect of family support on the physical health of the elderly in the village ofDusun III Hutarao shavings Airport District Island District in 2014. This research uses analyticaldesign with a cross-sectional design with Chi-Square Test to determine the effect of family support onthe physical health of the elderly in the village of Dusun III Hutarao Island County Airport Districtshavings. The population is elderly and samples obtained 37 elderly aged 60 years and older who arestill able to move. The result showed that the majority of informational support in less categories thataffect the physical health of the elderly with a value of p = 0.001, which means there is a connectioninformational support to the physical health of the elderly. On the support of a majority vote by bothcategories of the physical health of the elderly with p = 0.0810 which means it does not influence theassessment of physical health support elderly. On the support of the majority of the categories ofemotional support were less influence on the physical health of the elderly with a value of p = 0.004,which means there is a relationship between emotional support to the physical health of the elderly. Inthe category of family support mayorita obtained either with p = 0.026, which means there is theinfluence of family support on the physical health of the elderly. Research goal should be advised ofthe educational institutions in order to add material about the physical health of family support for theelderly and the results can be used as a reference for further research while for elderly people whohave to pay more attention or providing support to the elderly so that the physical health of the elderlycan be maintained better